Crowd-Workers: Aggregating Information Across Turkers to Help Them Find Higher Paying Work - Callison-Burch, Chris (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2014)
The Mechanical Turk crowdsourcing platform currently fails to provide the most basic piece of information to enable workers to make informed decisions about which tasks to undertake: what is the expected hourly pay? Mechanical Turk advertises a reward amount per assignment, but does not give any indication of how long each assignment will take. We have developed a browser plugin that tracks the length of time it takes to complete a task, and a web service that aggregates the information across many workers. Our web service, crowd-workers.com, allows workers to discovery higher paying work by sorting tasks by estimated hourly rate.